Spatial Behavior of a Coupled System of Wave-Plate Type - Gusheng Tang; Yan Liu; Wenhui Liao (Abstract and Applied Analysis)
The spatial behavior of a coupled system of wave-plate type is studied. We get the alternative results of Phragmén-Lindelöf type in terms of an area measure of the amplitude in question based on a first-order differential inequality. We also get the spatial decay estimates based on a second-order differential inequality.